Synthetic approaches to potent heterocyclic inhibitors of tuberculosis: A decade review - Dasmahapatra, Upala; Chanda, Kaushik (Frontiers in Pharmacology, 2022)
Tuberculosis (TB) continues to be a significant global health concern with about 1.5 million deaths annually. Despite efforts to develop more efficient vaccines, reliable diagnostics, and chemotherapeutics, tuberculosis has become a concern to world health due to the HIV, the rapid growth of bacteria that are resistant to treatment, and the recently introduced COVID-19 pandemic. As is well knowledge, the development of significant life-saving pharmaceuticals that have had a profound influence on patient lives and health across the globe has historically been made possible by discoveries in synthetic organic chemistry. Small molecule research as a novel chemical entity (NCE) for a specific disease target offers in-depth knowledge and potential therapeutic targets. In this viewpoint, we concentrated on the synthesis of a number of heterocycles reported in the previous decade as well as the screening of their inhibitory action against diverse strains of Mycobacterium TB. These findings offer specific details on the structure-based activity of several heterocyclic scaffolds backed by their in-vitro tests as a promising class of anti-tubercular medicines, which will be further useful to build effective treatments to prevent this terrible illness.